ANALYSIS OF PROBLEMS IN ORGANIZING INTERNAL AUDIT IN JOINT STOCK COMPANIES - Jumayeva, Gulrukh Jurakulovna; Yakhshikulova, Moxinur Toxir qizi (Educational Research in Universal Sciences, 2023)
This article describes the existing problems in the organization of internal audit in joint-stock companies, their analysis and the scientific basis of analytical approaches.